What Is the Most Cost-Effective Breeding Program for Lactating Dairy Cows—Timed AI, Estrous Detection, or a Combination of Both? - Klibs N. Galvão; Gustavo M. Schuenemann; Eduardo S. Ribeiro; Jose Eduardo P. Santos (EDIS, 2014)
As any other business enterprise, the sustainability of a dairy farm is highly dependent on economics. Reproduction influences both milk production and number of replacement heifers available on a farm; therefore, reproductive efficiency becomes a key determinant of dairy cow profitability. Several parameters affect reproductive performance. This 4-page fact sheet presents information from recently published articles that looked at the economics of different reproductive programs for breeding dairy cows that use estrus detection only, timed AI only, or a combination of both. Written by Klibs N. Galvão, Gustavo M. Schuenemann, Eduardo S. Ribeiro, and Jose Eduardo P. Santos, and published by the UF Department of Veterinary Medicine-Large Animal Clinical Sciences, May 2014.